“It’s wishy-washy [...] You are getting this diagnosis because we’ve ruled out everything else.” Developmental language disorder (DLD) diagnosis in the Republic of Ireland: A qualitative exploration of the perspectives of parents and clinicians - Sylwia Kazmierczak-Murray; Neil Kenny; Suzanne Carolan; Alison Doyle (PLoS ONE, 2025)
Developmental Language Disorder (DLD) affects around 7% of children globally, yet the scholarship on it is significantly underdeveloped. Emerging research suggests that DLD is both underdiagnosed by clinicians and misunderstood by parents. This study explores the perspectives of both clinicians and parents regarding their experiences of the process of giving and receiving a DLD diagnosis in the Republic of Ireland. Semi-structured qualitative group interviews were conducted with 15 parents and seven clinicians. The data were analysed using a reflexive, thematic analysis. Four themes were identified: “challenges of giving a DLD diagnosis”, “communicating a DLD diagnosis”, “utility of DLD diagnosis for children and families” and “going forward and recommendations”. Clinicians reported systemic barriers in the healthcare system, including limited therapy time, long waitlists, and staff turnover, as major challenges in diagnosing DLD. Many expressed a lack of confidence in providing a diagnosis without multidisciplinary support which would support them in ‘ruling out’ other neurodevelopmental differences. Communicating the diagnosis was often inconsistent, with many parents feeling unsupported and uninformed about the nature and impact of DLD. Parents felt inadequate at being left with communicating the diagnosis of DLD and its impact to their children. The participants emphasised urgent need for greater awareness, teacher and clinical education, post-diagnosis support, and increased national advocacy in relation to DLD in Ireland. Both clinicians and parents saw DLD diagnosis as essential for accessing therapeutic and educational support, yet it was the access to these supports that seemed to influence the diagnostic decisions. Importantly, our research documents clinicians’ fear of getting the “right” condition for diagnosis, which may be firstly at odds with the individual profiles of children, and secondly, acts as a barrier in accessing the needed support. In light of growing awareness of the co-occurrence of neurodevelopmental differences, we call for enhanced support for clinicians to build their confidence in navigating the evolving diagnostic criteria of DLD.